Anatomy, ontogeny, and evolution of the archosaurian respiratory system: A case study on Alligator mississippiensis and Struthio camelus. Issue 4 (20th December 2020) - Schachner, Emma R.; Hedrick, Brandon P.; Richbourg, Heather A.; Hutchinson, John R.; Farmer, CG
Abstract: The avian lung is highly specialized and is both functionally and morphologically distinct from that of their closest extant relatives, the crocodilians. It is highly partitioned, with a unidirectionally ventilated and immobilized gas‐exchanging lung, and functionally decoupled, compliant, poorly vascularized ventilatory air‐sacs. To understand the evolutionary history of the archosaurian respiratory system, it is essential to determine which anatomical characteristics are shared between birds and crocodilians and the role these shared traits play in their respective respiratory biology. To begin to address this larger question, we examined the anatomy of the lung and bronchial tree of 10 American alligators ( Alligator mississippiensis ) and 11 ostriches ( Struthio camelus ) across an ontogenetic series using traditional and micro‐computed tomography (µCT), three‐dimensional (3D) digital models, and morphometry. Intraspecific variation and left to right asymmetry were present in certain aspects of the bronchial tree of both taxa but was particularly evident in the cardiac (medial) region of the lungs of alligators and the caudal aspect of the bronchial tree in both species. The cross‐sectional area of the primary bronchus at the level of the major secondary airways and cross‐sectional area of ostia scaled either isometrically or negatively allometrically in alligators and isometrically or positively allometrically in ostriches with respect to body mass. Of 15 lung metrics, five were significantly different between the alligator and ostrich, suggesting that these aspects of the lung are more interspecifically plastic in archosaurs. One metric, the distances between the carina and each of the major secondary airways, had minimal intraspecific or ontogenetic variation in both alligators and ostriches, and thus may be a conserved trait in both taxa. In contrast to previous descriptions, the 3D digital models and CT scan data demonstrate that the pulmonary diverticula pneumatize the axial skeleton of the ostrich directly from the gas‐exchanging pulmonary tissues instead of the air sacs. Global and specific comparisons between the bronchial topography of the alligator and ostrich reveal multiple possible homologies, suggesting that certain structural aspects of the bronchial tree are likely conserved across Archosauria, and may have been present in the ancestral archosaurian lung. Abstract : Quantitative comparisons between the bronchial trees of the alligator and ostrich reveal multiple possible homologies, suggesting that certain structural aspects of lungs are likely conserved, and may have been present in the ancestral archosaurian lung. Additionally, CT data show that the post‐cranial skeleton of the ostrich is pneumatized from pulmonary diverticula emerging directly from the gas‐exchanging lung in some regions, and not always directly from the air sacs.